2016
DOI: 10.1093/mnras/stw3209
|View full text |Cite
|
Sign up to set email alerts
|

The SILCC project – III. Regulation of star formation and outflows by stellar winds and supernovae

Abstract: We study the impact of stellar winds and supernovae on the multi-phase interstellar medium using three-dimensional hydrodynamical simulations carried out with FLASH. The selected galactic disc region has a size of (500 pc) 2 × ±5 kpc and a gas surface density of 10 M pc −2 . The simulations include an external stellar potential and gas self-gravity, radiative cooling and diffuse heating, sink particles representing star clusters, stellar winds from these clusters which combine the winds from individual massive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
191
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(208 citation statements)
references
References 127 publications
(116 reference statements)
16
191
0
1
Order By: Relevance
“…18), as it is the over-pressurized hot gas that drives the outflows. Our result is in very good agreement with recent studies such as Walch et al (2015), Girichidis et al (2016b) or Gatto et al (2017). In addition to the effect of photoionization, we find that the adopted stellar lifetime also has an important effect on nSNII.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…18), as it is the over-pressurized hot gas that drives the outflows. Our result is in very good agreement with recent studies such as Walch et al (2015), Girichidis et al (2016b) or Gatto et al (2017). In addition to the effect of photoionization, we find that the adopted stellar lifetime also has an important effect on nSNII.…”
Section: Discussionsupporting
confidence: 93%
“…Including photoionization helps suppress star formation, as PE-PI-SN-cmp and noPE-PI-SNcmp both show much lower SFRs. This highlights the importance of feedback from massive stars prior to their SN events on regulating star formation in the higher gas surface density regime (see also Gatto et al (2017) who investigated the importance of stellar winds in a Milky Way setup). The fact that PE-PI-SN-cmp and noPE-PI-SN-cmp both have very similar SFR is consistent with our previous study in Paper I where we found that the SFR in dwarf galaxies is insensitive to the adopted value of G0 (constant field).…”
Section: Global Propertiesmentioning
confidence: 73%
See 2 more Smart Citations
“…These results illustrate the importance of considering FUV feedback in understanding the star formation activity of galactic disk systems. Similar conclusions have been reached by Peters et al (2017) in their lower (4 pc) resolution studies of a smaller (0.5 kpc by 0.5 kpc) disk patch, which builds on the previous study of a stellar wind and supernova feedback model by Gatto et al (2017).…”
Section: Discussionsupporting
confidence: 85%